Peran Keberfungsian Keluarga terhadap Psychological Well-Being pada Narapidana Anak di LPKA Kelas II Maros dengan Resiliensi sebagai Mediator - Putri Aura Ibdaria Sudirman; Muhammad Ilham; Risha Diva Sari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Juvenile inmates are a vulnerable population who face complex psychological challenges due to separation from family, social stigma, and adaptation to correctional environments. Family functioning is considered an important factor that may support adolescents’ psychological well-being, while resilience is often viewed as a protective mechanism in coping with adverse conditions. This study aimed to examine the mediating role of resilience in the relationship between family functioning and psychological well-being among juvenile inmates at LPKA Class II Maros. A quantitative approach was employed using a total sampling technique involving 62 juvenile inmates. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results indicated that family functioning had a positive and significant effect on resilience (Î² = 0.460; p < 0.001). However, family functioning did not significantly affect psychological well-being (Î² = 0.218; p = 0.241), and resilience also showed no significant effect on psychological well-being (Î² = 0.120; p = 0.644). Furthermore, resilience was not found to mediate the relationship between family functioning and psychological well-being (Î² = 0.055; p = 0.676). These findings suggest that although supportive family functioning contributes to the development of resilience, resilience alone is insufficient to directly enhance psychological well-being among juvenile inmates. The results indicate that psychological well-being in this high-risk population may be influenced by other psychosocial factors beyond family functioning and resilience, such as social support, coping strategies, and institutional environments. This study contributes to the understanding of psychological well-being among juvenile inmates and highlights the importance of considering broader psychosocial interventions in correctional settings.